CONTEMPLATIVE DIMENSION OF OSHO’S VISION AND HIS WORK - Vedant, Swami Satya (Journal of Dharma, 1992)
Today there are only two alternatives before mankind: either man commits a global suicide or the whole humanity takes a quantum leap in a new consiousness. This is a critical moment. Not only man, but the entire planet is under threat. Nuclear weapons, the population explosion, the ecological disasters, the killer-disease AIDS and above all the man himself have created such horrendous problems that only a radical shift in human consciousness can save Fife on this beautiful planet earth.